ANALISIS KONTEN PEMBERITAAN INTERAKSI MANUSIA-SATWA PREDATOR DI INDONESIA - Ardiantiono Ardiantiono; Afrizal Maula Alfarisi; Yanuar Ishaq; Rhemawati Wijaya; Reza Septian; Adhi Nurul Hadi (Jurnal Belantara, 2022)
Media reports on human-predator interaction can influence public attitudes and supports toward wildlife conservation. Negative interactions between humans and wildlife in Indonesia are dominated by two predator species: Sumatran tiger (Panthera tigris sumatrae) and saltwater crocodile (Crocodylus porosus). This research aims to characterize the patterns of media reporting on human-predator interaction and compare the reporting between tiger and crocodile. Media reports published between 2017-2019 were collected from online mass media using Google News searching tool. Four parameters were used to evaluate the media content: tone, framing, illustration, and objectivity. Reports on human-tiger interaction (HTI; 356 articles) and human-crocodile interaction (HCI; 430 articles) showed similar patterns including dominant negative headline tone, neutral reporting focusing on interaction events, use of neutral-safe illustrations, and objective reporting. Further investigation showed that some aspects of media reporting on HCI differed from HTI. Reporting on HTI incidents used more negative contents and illustrations; and was not as comprehensive as HTI reporting. To promote balanced reporting, this research recommends collaboration between practitioners, scientists, and media to increase the media awareness on human-predator interactions and wildlife conservation; to write engaging content; and to increase the roles of practitioners and scientists as writers and sources in mass media.